Be like water, my cells: cell plasticity and the art of transformation - Cammareri, Patrizia; Myant, Kevin B. (Frontiers in Cell and Developmental Biology, 2023)
Cellular plasticity defines the capacity of cells to adopt distinct identities during development, tissue homeostasis and regeneration. Dynamic fluctuations between different states, within or across lineages, are regulated by changes in chromatin accessibility and in gene expression. When deregulated, cellular plasticity can contribute to cancer initiation and progression. Cancer cells are remarkably plastic which contributes to phenotypic and functional heterogeneity within tumours as well as resistance to targeted therapies. It is for these reasons that the scientific community has become increasingly interested in understanding the molecular mechanisms governing cancer cell plasticity. The purpose of this mini-review is to discuss different examples of cellular plasticity associated with metaplasia and epithelial-mesenchymal transition (EMT) with a focus on therapy resistance.